United Nations Environment Program (UNEP) Efforts to Help India on Managing Urban Solid Waste Pollution Issues (2013 – 2020): United Nations Environment Program (UNEP) Efforts to Help India on Managing Urban Solid Waste Pollution Issues (2013 – 2020) - paramitaningrum; Holga Nathanael Gunung (Jurnal Asia Pacific Studies, 2024)
Abstract This research analyzes the efforts of The United Nations Environmental Programme (UNEP) in assisting the Indian government in addressing environmental pollution issues. India has been fighting against waste pollution for decades. Pollution in India has reached alarming levels as its massive impacts have spread to various aspects of life and the environment. The Indian government has implemented several policies related to this issue, some of which have been successful, and they will continue their efforts. Additionally, local and international organizations contribute by engaging in collaborative efforts targeting communities and the environment. One of these organizations is the United Nations Environment Programme, a United Nations body focused on environmental issues. However, sustained efforts are still needed to address this problem and achieve meaningful results. The research methodology is qualitative, and the data collection method is secondary. Data is gathered from academic journals, news sources, and relevant books from valid sources. The author utilizes the theory of Neoliberal Institutionalism to analyze this research. Keywords: Urban Solid Waste Pollution, Waste Management System, The United Nations Environmental Programme (UNEP), Neoliberal Institutionalism